Movimentos sociais e processos estruturais no Supremo Tribunal Federal: a participação social no âmbito da arguição de descumprimento de preceito fundamental - Barsoumian, Amanda Pilon (2026)
This research is grounded on the context of liberal democracy with the objective of analyzing the action of social movements upon the Federal Supreme Court exploring how this social actor relates to the structure of the Constitutional Court and, conversely, the effects of this structure on the shaping and actions of social movements. The Claim of Non-Compliance with a Fundamental Precept (ADPF), structural in nature, brings to the attention of the Federal Supreme Court complex realities that result in serious and systematic violations of fundamental rights. These realities, in turn, give rise to strong and articulated social movements, which aim to overcome illegalities and constitutional violations through multiple strategies for action, including judicial interventions. Given this context, this investigation explores and describes this recent phenomenon of organized social participation of social movements in structural constitutional actions. This interdisciplinary research draws on knowledge traditionally compartmentalized across legal, social, and political sciences. It starts with a literature review of the main authors in social and legal theory, in order to establish the state of the art concerning social movements and structural processes. It also provides an in-depth analysis of the proposed theme. In addition, to verify the occurrence of this phenomenon in the practice of the Federal Supreme Court, empirical research was conducted based on legal documents, especially the case files of the structural ADPFs currently pending before the Court. This research aims to understand how social movements relate to the Constitutional Court and to present the important advancements resulting from the introduction of structural actions in that institution